Valsartan combined with clopidogrel and/or leflunomide for the treatment of progressive immunoglobulin A nephropathy. (February 2015) - Cheng, Genyang; Liu, Dongwei; Margetts, Peter; Liu, Limin; Zhao, Zhanzheng; Liu, Zhangsuo; Tang, Lin; Fang, Yudong; Li, Haijian; Guo, Yuanyuan; Chen, Fengmei; Liu, Fengxun
Abstract Aim The current standard treatment for IgA nephropathy relies on steroid and/or immunosuppressive therapy and angiotensin converting enzyme inhibitors (ACEI) or angiotensin receptor blocker (ARB). This study examines the benefits and safety of combining valsartan with clopidogrel and leflunomide as a treatment for progressive IgA nephropathy. Methods Patients with primary IgA nephropathy, confirmed by renal biopsy, were recruited for this study. Patients were separated into four groups (n = 42 each) after 2 months of run‐in period of valsartan treatment. All patients were treated with valsartan alone (Group 1) or valsartan and either clopidogrel (Group 2) or leflunomide (Group 3) or both clopidogrel and leflunomide (Group 4). Each group was followed up for their next 24 months for 24 h urinary protein excretion, serum creatinine and estimated glomerular filtration rate (eGFR) to assess the effect of the treatment. Adverse effects were recorded concurrently to evaluate the safety of the treatment. Results Of all 168 patients, 107 were males and 61 were females, with an average age of 33.8 ± 8.79 years. Baseline characteristics were comparable among the four groups (P > 0.05) prior to the experimental treatment. There was a significant (P < 0.05) decrease in 24 h urinary protein excretion after 4 months of experimental treatment. At the end of the 24 months, groups 3 and 4 showed a respective 62.35% and 69.47% reduction in proteinuria. The serum creatinine was significantly higher (P < 0.05) in group 1 and 2 at the end of the follow‐up, and their respective eGFR was significantly lower. The incidence of cardiovascular complication was 11.9% and 9.5% for group 1 and 3, respectively. Conclusions The treatment with Valsartan combined with Clopidogrel and Leflunomide can reduce the urinary proteins loss and renal function deterioration for IgA nephropathy patients and cause minimal adverse reactions. Our study suggests a new clinical treatment option for IgA nephropathy.